Robotic and Laparoscopic Approaches for Adrenal Surgery in Obese Patients. Issue 4 (April 2021) - Shalaby, Hosam; Abdelgawad, Mohamed; Omar, MD, Mahmoud; Zora, MD, Ghassan; Alawwad, Saad; Alameer, Ehab; Youssef, Mohanad; Attia, Abdallah S.; Buell, Joseph; Grace, Lee; Kandil, Emad
Objective: Minimally invasive adrenalectomy is a challenging procedure in obese patients. Few recent studies have advocated against robot-assisted adrenalectomy, particularly in obese patients. This study aims to compare operative outcomes between the robotic and laparoscopic adrenalectomy, particularly in obese patients. Materials and Methods: A retrospective analysis was performed on all consecutive patients undergoing adrenalectomy for benign disease by a single surgeon using either a laparoscopic or robotic approach. Adrenal surgeries for adrenal cancer were excluded. Demographics, operative time, length of hospital stays, estimated blood loss (EBL), and intraoperative and postoperative complications were evaluated. Patients were divided into 2 groups; obese and nonobese. A sub-analysis was performed comparing robotic and laparoscopic approaches in obese and nonobese patients. Results: Out of 120, 55 (45.83%) were obese (body mass index ≥ 30 kg/m 2 ). 14 (25.45%) of the obese patients underwent a laparoscopic approach, and 41 (74.55%) underwent a robotic approach. Operative times were longer in the obese vs. nonobese groups (173.30 ± 72.90 minutes and 148.20 ± 61.68 minutes, P = .04) and were associated with less EBL (53.77 ± 82.48 vs. 101.30 ± 122, P = .01). The robotic approach required a longer operative time when compared to the laparoscopic approach (187 ± 72.42 minutes vs. 126.60 ± 54.55 minutes, P = .0102) in the obese but was associated with less blood loss (29.02 ± 51.05 mL vs. 138.30 ± 112.20 mL, P < .01) and shorter hospital stay (1.73 ± 1.23 days vs. 3.17 ± 1.27 days, P < .001). Conclusion: Robot-assisted adrenal surgery is safe in obese patients and appears to be longer; however, it provides improvements in postoperative outcomes, including EBL and shorter hospital stay.